The roticulating concept air compressor: experimental and numerical investigation. (August 2019) - Zhang, Y; Madamedon, M; Copeland, C; Fenton, J P; Subert, J; Hinchliffe, K; Arbon, I M; Leefe, S
Abstract: This paper documents the first prototype tests of the FeTu bare-shaft oil-free air compressor, conducted over a one-year study at the University of Bath, with funding support from Innovate UK. Giving feasibility to the concept and to provide an initial indicator of its performance, in terms of pressure capability, isentropic efficiency and specific power demand as an oil-free air compressor. A range of 6 units in total were validated on a continuous flow test-rig, with variations on internal sealing, internal clearance, and Non-Return Valve (NRV) settings, to assess their impact on volumetric efficiency, in pursuit of an optimal design. Tests covered a speed range of 100 rpm-1500 rpm and reached discharge pressures up to 6 barg, results indicated that the compressor can maintain a 50% torque-based efficiency between a pressure ratio (PR) of 1.5 to 2.8. Tests reveal low compressed gas temperature of 125ºC at 2.8PR, which gave rise to a high isentropic efficiency of over 80%, therefore specific power was adopted as the main Key Performance Indicator (KPI).